2015
DOI: 10.1002/2014ja020503
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the lower hybrid drift instability at reconnection jet front

Abstract: We investigate current‐driven modes developing at jet fronts during collisionless reconnection. Initial evolution of the reconnection is simulated using conventional 2‐D setup starting from the Harris equilibrium. Three‐dimensional PIC calculations are implemented at later stages, when fronts are fully formed. Intense currents and enhanced wave activity are generated at the fronts because of the interaction of the fast flow plasma and denser ambient current sheet plasma. The study reveals that the lower hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
90
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(104 citation statements)
references
References 71 publications
10
90
1
Order By: Relevance
“…Note that there are already several DF observations by MMS with a small separation close to 40 km (e.g., Liu et al, 2018). However, these finger-like density structures arising from kinetic instabilities are at ion-electron hybrid scale (e.g., Divin, Khotyaintsev, Vaivads, André, Markidis, et al, 2015;Vapirev et al, 2013), larger than the scale of the density gradient we observed in the low-density side of the DF. More importantly, these observations did not investigate the electron-scale current, electric structure, and energy conversion using multispacecraft method.…”
Section: Summary and Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Note that there are already several DF observations by MMS with a small separation close to 40 km (e.g., Liu et al, 2018). However, these finger-like density structures arising from kinetic instabilities are at ion-electron hybrid scale (e.g., Divin, Khotyaintsev, Vaivads, André, Markidis, et al, 2015;Vapirev et al, 2013), larger than the scale of the density gradient we observed in the low-density side of the DF. More importantly, these observations did not investigate the electron-scale current, electric structure, and energy conversion using multispacecraft method.…”
Section: Summary and Discussionmentioning
confidence: 57%
“…To date, DF structure at ion scale has been well investigated by spacecraft observations and numerical simulations (e.g., Balikhin et al, 2014;Drake et al, 2014;Divin, Khotyaintsev, Vaivads, André, Markidis, et al, 2015;Fu et al, 2012a;Pritchett et al, 2014;Vapirev et al, 2013;Yao et al, 2016), while DF structure at electron scale still remains not fully understood due to instrumental limitations and spacecraft separation distances. Studying the DF dynamics is of particular interest for the magnetotail physics.…”
Section: Introductionmentioning
confidence: 99%
“…The front is again subject to the same instability as described above and driven by the density gradients at the fronts. A detailed investigation of the nature of the instability in the present run and discussed in previous research 34,41 is reported in the Supplementary Methods. Although the nature of the instability is the same as in Run A, the nonlinear evolution presents some differences owing to the different box size and boundary conditions.…”
Section: Secondary Reconnection In Reconnection Frontsmentioning
confidence: 89%
“…32) and kinetic 33 simulations. When considered at the kinetic level, this instability acquires the nature of a drift instability caused by the presence of drifts associated with the density gradients 34 . An in-depth analysis of the nature of the instability as well its energetic consequences is provided in the Supplementary Information.…”
Section: Simulation Of Reconnection-generated Flux Ropesmentioning
confidence: 99%
“…The nature of this instability is that of a drift mode [15,12]: the density at the front has a strong gradient in a direction normal to the field, the typical condition for drift modes [12]. We reported elsewhere the analysis of the mode spatial and temporal spectrum [7].…”
Section: Drift-interchange Destabilization Of Fronts Formed By Reconnmentioning
confidence: 99%